Bystander resuscitation of a near-drowning child in a rural south China township. Issue 4 (1st December 2013) - Wu, Zhixin; He, Mingfeng; Guo, Qihong; Kuang, Minhua
Abstract : We report resuscitation of a near-drowning child by a bystander in a rural south China township. Resuscitation was performed on a 6-year-old, otherwise healthy boy who was witnessed drowning in a river, with submersion for approximately 12 min. Following several resuscitation attempts, spontaneous breathing was established at the scene and the boy was transferred to a nearby hospital. He developed pneumonia but recovered completely on the ward and was discharged without any neurologic disabilities. This case shows that early bystander resuscitation is an important factor for survival after submersion. The search for an ideal approach to resuscitation must continue, and all members of society must work together towards this goal.